Impact of Environmental Changes on Biodiversity in Westernmost Part of West Bengal (India) - Basu, Ramsankar (Indian Forester, 2016)
To the westernmost part of the state of West Bengal in India, under the eastern fringe of Chhota Nagpur plateau, the district of Purulia and Bankura are marked with hills and hillocks, dense forested areas, high altitude, hot summer, metamorphic calcareous rocks and tropical dry deciduous monsoon vegetation. Schedule castes, tribes and other backwards are majority in population. A mass of them are dependent on forests resources partially or completely. Destruction of forest territories, unsustainable practice of forest resources, diversion of forest areas for industrialization like stone crusher, brick clin, quarries and coal mines, limestone, cement, alloy stil and sponge iron workshop in private sectors and thermal power plants in government sectors are causing destruction of the environmental balance through climate change. Excess exploitation of nature affects upon biological resources and life sustaining system. Human activities have changed ecosystem more rapidly and creating problem upon the flora and fauna, people’s livelihood. It affects the biodiversity. It causes increasement of level of gases like CO, CO2, SO, SO2, NO, NO2, N2O and exude PAN through automobiles. The present paper discusses on various causes responsible for the loss in biodiversity due to change in environment and developing ways of mitigating such effects.